LIMBAH PEMANENAN DAN FAKTOR EKSPLOITASI IUPHHK-HA PT. RIZKI KACIDA REANA–KABUPATEN PASER PROVINSI KALIMANTAN TIMUR - Asep Mansur (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
The purpose of this study was to determine and quantify waste harvesting and exploitation factors IUPHHKA-HA PT. Rizki Kacida Reana Tajur Village, District Long Ikis, Paser Regency, East Kalimantan Province for 1 month in June and July 2013.Experiments in coupe IUPHHK-HA PT. Rizki Kacida Reana RKT 2013 with a sample of 50 trees on the 3 coupe and the data collected is primary data in the form of observations and measurements of length and diameter of trees that have fallen felled to obtain results which are expected to be utilized tree volume up to the first branch and stem volume not utilized, while the secondary data obtained directly from IUPHHK-HA PT. Rizki Kacida Reana and from the literature that supports.The results obtained are 1). The percentage of waste timber harvesting of species bangkirai 18.09%, 21.69% kapur types, types keruing 15.39%, 16.25% meranti merah, meranti putih 10.98%, and 34.79% rimba campuran types. Percentage of waste timber harvesting on average is equal to 14.73%. 2). Exploitation of timber harvesting factor IUPHHK-HA PT. Rizki Kacida Reana from 0.83 bangkirai types, types of kapur 0.82, 0.84 keruing type, 0.86 meranti merah, meranti putih 0.90, 0.69 rimba campuran types, so that the average size is 0.86 this was in accordance with that stipulated by the Ministry of Forestry Republic of Indonesia using 0.8 exploits factor in determining the level of annual production, and twenty-five-year annual. 3). Optimizing the use of waste as a whole can be used, either in the form of wood and a small scale as household firewood.